Etude de la qualité des oeufs de deux génotypes de pondeuses (locales et sélectionnées). Estimation des corrélations phénotypiques - DILMI, SAMIRA (My University, 2018)
On the whole, 59 eggs ( from 20 industrial and 39 local laying hens) were the object of this study; it considers the quality of eggs resulting from two genotypes , and the phenotypic correlations between the various internal and external parameters of eggs. The results show that in terms of the proportions of the three components of the egg (shell, yolk, white), no significant difference (P≥0.05) was observed between the two studied genotypes. from one hand, in local hens, the estimate of the phenotypic correlations between the parameters of the eggs show that the three principal components of the eggs noted that endosperm displayed the strongest relationship to the weight of the whole egg (+0,858; P<0,001). From the other hand, the phenotypic correlations between the internal and external parameters of eggs of industrial stock vary between -0.01 and - 0.74. So, the strongest negative correlation was noted between both of the form and the length of eggs. By using the best model selected, it was recognized that in both genotypes, the whole weight of the egg can be useful for the prediction of the weight of the endosperm, it is actually more important to local hens than the industrial ones (R ² = 0.73against R ² = 0.27). However, the coefficients of determination obtained for the prediction of the weight of the yolk only were very low (R ² =0.27 and R ² =0.07) respectively for both local and the commercial hens.
Keywords: laying hens.; genotypes; eggs; quality; phenotypic correlations.pondeuses; génotypes; oeufs; qualité; corrélations phénotypiques